2021
DOI: 10.2106/jbjs.cc.20.00988
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Nocardiosis Masquerading as Soft-Tissue Malignancy

Abstract: Case: A 59-year-old man, immunosuppressed after renal transplant, presented with a painful posterior thigh mass concerning for malignancy, as well as pulmonary and posterior chest wall nodules. Cultures and mass spectrometry identified Nocardia paucivorans. The patient underwent operative irrigation and debridement of the posterior thigh and chest wall, with 12 months of antibiotic therapy. Conclusion: A 2-week delay in appropriate treatment was due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…When the central nervous system (CNS) is involved, patients may also experience headaches, confusion, and seizure [ 10 ]. Once disseminated, nocardiosis can resemble findings of metastatic malignancy [ 6 , 15 ]. One such report by Wuthrich et al involved N. paucivorans infection in a renal transplant recipient, similar to our case [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When the central nervous system (CNS) is involved, patients may also experience headaches, confusion, and seizure [ 10 ]. Once disseminated, nocardiosis can resemble findings of metastatic malignancy [ 6 , 15 ]. One such report by Wuthrich et al involved N. paucivorans infection in a renal transplant recipient, similar to our case [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once disseminated, nocardiosis can resemble findings of metastatic malignancy [ 6 , 15 ]. One such report by Wuthrich et al involved N. paucivorans infection in a renal transplant recipient, similar to our case [ 6 ]. The authors reported that a 59-year-old male with a history of renal transplant for kidney disease due to vasculitis presented with a painful thigh mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations